Dissociating Sensory and Cognitive Biases in Human Perceptual Decision-Making: A Re-evaluation of Evidence From Reference Repulsion - Kuang, Shenbing (Frontiers in Human Neuroscience, 2019)
Our perception of the world is governed by a combination of bottom-up sensory and top-down cognitive processes. This often begs the question whether a perceptual phenomenon originates from sensory or cognitive processes in the brain. For instance, reference repulsion, a compelling visual illusion in which the subjective estimates about the direction of a motion stimulus are biased away from a reference boundary, is previously thought to be originated at the sensory level. Recent studies, however, suggest that the misperception is not sensory in nature but rather reflects post-perceptual cognitive biases. Here I challenge the post-perceptual interpretations on both empirical and conceptual grounds. I argue that these new findings are not incompatible with the sensory account and can be more parsimoniously explained as reflecting the consequences of motion representations in different reference frames. Finally, I will propose one concrete experiment with testable predictions to shed more insights on the sensory vs. cognitive nature of this visual illusion.